SOURCE LANGUAGE VERSUS TARGET LANGUAGE TRANSLATION PROCEDURES - AKHMAD BAIHAQI (Journal of English Language Teaching and Literature (JELTL), 2018)
The objective of the research was to gain deep understanding of the translation procedures that occurred at the students’ translation texts from English to Indonesian language in English Study Program of Teachers Training and Education College of Syekh Manshur in 2017. This research was conducted through qualitative content analysis. Data of the research were taken from the documentation of students’ translation text; then, they were analyzed through the model of inductive category development. The result of the research showed that from total of 18 translation texts that had been analyzed, it was found there were 9 texts or 49.99 % applied source language emphasized procedures, and 3 texts or 16.66 % applied target language emphasized procedures. The research concludes that the existence of translation procedures in the translation process depends on either a problem in translating or the intention of naturalness.